Determinants of Consumers' Choice and Willingness to Pay for Biofortified Pearl Millet in Kenya. Issue 2 (2nd October 2017) - Ongudi, Silas O.; Ngigi, M.W.; Kimurto, P.K.
ABSTRACT: Globally, micronutrient deficiency is a major health concern as more than two billion people suffer from iron deficiency, 1.75 billion are at risk of low zinc intake, while 127 million pre-school children suffer from vitamin A deficiency. Consumption of iron biofortified pearl millet is one optimal strategy for reducing micronutrient deficiencies, which is a major health concern. However, its consumption is unclear due to changes in product traits (appearance, aroma and flavour) from biofortification. Therefore, we centred on the hypothetical introduction of a biofortified pearl millet variety in Mbeere District, Kenya, where most staple crops record poor yields. We used a contingent valuation method in estimating consumer willingness to pay (WTP), on a sample of 100 biofortified pearl millet consumers. Our findings indicate that consumers were willing to pay an average premium of 42 percent above the prevailing market price of finger millet varieties. Factors directly influencing WTP were: frequency of consuming finger millet; whether consumer is a household decision maker or otherwise; household income and consumer's previous experience; and level of awareness concerning the benefit of consuming biofortified pearl millet products. These results suggest the need for market segmentation with more attention given to high-income households with good knowledge of pearl millet in promoting biofortified pearl millet products.